Effect of Ginger on Primary Dysmenorrhea - Rahayu Yekti Maryanto (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Abstract Menstruation is an effect of the destruction of the endometrium. Menstrual disorders that often occur are dysmenorrhea. Dysmenorrhea is a gynecological disorder due to the instability of the hormone progesterone in the blood, resulting in pain and often occurs in women. Dysmenorrhea is abdominal pain that comes from uterine cramps and occurs during menstruation. This menstrual pain occurs periodically on menstrual days. Menstrual pain is the most common problem in adolescent and adult women. Menstrual disorders as a health problem for women not only affect reproductive health, but also psychological health and quality of life. Menstrual pain during primary dysmenorrhea is an inconvenience for women around the world that can cause difficulty in carrying out daily life activities. This paper aims to explore the literature on the non pharmacological benefits of natural herbs used to relieve primary dysmenorrhea pain. Previous studies have shown that ginger is very effective in relieving primary dysmenorrhea menstrual pain. Keywords: Ginger, Dysmenorrhea, Natural herbs, menstrual pain.